Production Performance and Nutritional Quality of Black Soldier Fly Larvae Nurtured in Different Organic Waste (Journal of Science and Technology Research, 2024)
Nutritionists are beginning to pay attention to black soldier fly (Hermetia illucens L.) larvae (BSFL) as an alternative to expensive soybean and fish meal in animal feed which is abundant in different nutrients. Additionally, organic wastes including leftover food, animal excreta, and agricultural wastes, can be used to efficiently raise and spread BSFL. This study was carried out to evaluate the yield, production performance and proximate composition of BSFL nurtured on different organic waste namely, broiler starter feed (BF); rice bran (RB); market-sourced vegetable wastes (VW); chicken manure (CM) and kitchen waste (KW). The BF fed group had the highest observed larval yields (16.2 kg in total; P